Characterization of Empty Fruit Bunch Treated with Ionic Liquid Prior to Enzymatic Delignification - Financie, Revie; Moniruzzaman, Muhammad; Uemura, Yoshimitsu (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2015)
The technological utility of enzymes for delignification can be increased by using ionic liquid to open more accessible surface area for biomass transformation into bio-based products. The present paper demonstrates application of ionic liquid (IL) [emim][DEP] 1-ethyl-3 methyllimidazolium-diethyl phospate for empty fruit bunch (EFB) pretreatment process followed by enzymatic delignification by using Laccase. It was found that [emim][DEP] increased the performance of the enzyme laccase and henced higher cellulose rich materials, whereas also reduced the lignin content in the EFB. The lowest lignin content obtained from IL-laccase treated EFB was approximately 17.92%, lower than the lignin content in the untreated EFB. Both treated and untreated EFB were characterized in chemical and physical properties by using scanning electron microscope (SEM), fourier transform infrared (FTIR), and thermogravimetric analysis (TGA/DTG) to observe the changes resulted from the pretreatment.